2017
DOI: 10.12659/ajcr.903539
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Presentation of Acute Fibrinous and Organizing Pneumonia

Abstract: Patient: Female, 56Final Diagnosis: Acute fibrinous and organizing pneumoniaSymptoms: Cough • dyspnea • feverMedication: —Clinical Procedure: —Specialty: PulmonologyObjective:Rare diseaseBackground:Acute fibrinous and organizing pneumonia (AFOP) is a newly evolving rare non-infectious lung pathology, characterized by intra-alveolar fibrin balls on histology. It is often difficult to diagnose and is usually mistaken for other lung pathologies. We present an interesting case of AFOP with unusual radiologic findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Cavitation is rare in organising pneumonia and to our knowledge it has never been reported in acute fibrinous organising pneumonia. Our patient had left upper lobe infiltrate with cavitation, in contrast to most cases presenting as bilateral basilar infiltrates 2 4 5 7. Such presentation brings up mycobacterial and fungal disease among the top differential diagnoses, which were ruled out in our patient.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Cavitation is rare in organising pneumonia and to our knowledge it has never been reported in acute fibrinous organising pneumonia. Our patient had left upper lobe infiltrate with cavitation, in contrast to most cases presenting as bilateral basilar infiltrates 2 4 5 7. Such presentation brings up mycobacterial and fungal disease among the top differential diagnoses, which were ruled out in our patient.…”
Section: Discussionmentioning
confidence: 59%
“…Other CT findings include peribronchovascular opacities, band-like consolidation, pleural effusion, solitary nodule and reverse halo sign 4 5. Jabbour et al 7 reported a case of acute fibrinous organising pneumonia with an unusual finding of upper lobe infiltrate. Cavitation is rare in organising pneumonia and to our knowledge it has never been reported in acute fibrinous organising pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] reported that the amount of chronic inflammatory cell infiltration surrounding the fibrin balls in AFOP lesions varies and noted that AFOP may be associated with lung infection. AFOP may improve following antibiotic treatment [ 14 ], suggesting that infection may trigger the onset of AFOP. Previous reports have shown that a variety of infections may be associated with AFOP, including bacterial infections ( Haemophilus influenzae , Acinetobacter baumannii ), viral infections (respiratory syncytial virus, influenza virus A/H1N1, human immunodeficiency virus), and fungal infections ( Pneumocystis jirovecii , Penicillium citrinum ) [ 1 , 5 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] suggested that alveolar epithelial cell injury caused by Legionella infection and subsequent tissue repair are involved in the pathology of OP and the development of its imaging manifestations. After alveolar injury, proteins and serous fluid in the capillaries enter the alveolar cavity, where they may be involved in fibrin ball formation [ 14 ]. This may explain the AFOP manifestations in the lungs of this patient.…”
Section: Discussionmentioning
confidence: 99%